Wage Bargaining and Capital Accumulation: A Dynamic Version of the Monopoly Union Model - Marco Guerrazzi (Global Labor Organization (GLO), 2024)
In this paper, I explore the relationship between wage bargaining and capital accumulation by developing a differential game in which a monopolistic union sets the wage of its members by taking as given the optimal employment strategy of a representative firm and the way in which capital is evaluated over time. Under the assumption that investment amounts to a constant share of produced output, I show that a meaningful open-loop Stackelberg equilibrium requires the union to be more patient than the firm. Moreover, relying on some numerical simulations, I show that although adjustments towards the steady-state equilibrium occur through damped oscillations, after an initial period of decline, the model predicts a stable union wage premium.
Keywords: J31; J51; J52; 330; Monopoly union model; Capital accumulation; Binding wage contracts; Differential games; Open-loop Stackelberg equilibrium